2017
DOI: 10.1038/s41598-017-07718-3
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial troponoids, puberulic acid and viticolins; divergent synthesis and structure-activity relationship studies

Abstract: Divergent synthesis of antimalarial troponoids, including naturally occurring compounds, some of which were identified and isolated by our group, has been achieved utilizing the total synthetic route of puberulic acid. Structure-activity relationships of natural products and simple troponoids inspired us to explore more detailed properties of this class of compounds. Access to new derivatives was facilitated through intermediate compounds generated during the total synthesis of puberulic acid by a stepwise oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…16,27 Colchicine derivatives also hold some promise as immunosuppressive agents. 28 Compounds embodying the -hydroxy--tropolone motif (30) (Figure 6), and that not only include puberulic acid (17) and manicol (19) (see above) but also puberulonic acid (31) and the xenovulene A metabolite 32, are notable for their broad range of biological activities that include anti-malarial, 12,29 antibacterial, 30 anti-fungal 31 and anti-viral ones. 32 The benzotropolone purpurogallin (33) (Figure 7), a readily prepared synthetic analogue 34 and the natural product -thujaplicin (13) have each recently been reported to display usefully selective cytotoxic properties.…”
Section: Medicinal Chemistry Aspects Of Troponoid Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,27 Colchicine derivatives also hold some promise as immunosuppressive agents. 28 Compounds embodying the -hydroxy--tropolone motif (30) (Figure 6), and that not only include puberulic acid (17) and manicol (19) (see above) but also puberulonic acid (31) and the xenovulene A metabolite 32, are notable for their broad range of biological activities that include anti-malarial, 12,29 antibacterial, 30 anti-fungal 31 and anti-viral ones. 32 The benzotropolone purpurogallin (33) (Figure 7), a readily prepared synthetic analogue 34 and the natural product -thujaplicin (13) have each recently been reported to display usefully selective cytotoxic properties.…”
Section: Medicinal Chemistry Aspects Of Troponoid Compoundsmentioning
confidence: 99%
“…Compounds embodying the α′-hydroxy-α-tropolone motif ( 30 ) (Figure 6 ), that not only include puberulic acid ( 17 ) and manicol ( 19 ) (see above) but also puberulonic acid ( 31 ) and the xenovulene A metabolite 32 , are notable for their broad range of biological activities that include antimalarial, 12 29 antibacterial, 30 antifungal 31 and antiviral ones. 32…”
Section: Medicinal Chemistry Aspects Of Troponoid Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Meanwhile, HSV-1 pUL12 has alkaline nuclease activity essential for in vivo function. 20 One challenge associated with developing aHTs as drugs has been the scarcity of synthetic methods available to make structural variants of them, 21 and up until very recently 22 all synthetic chemistry-driven structure-function studies on the chemotype relied on direct modication of either 3,7-dihydroxytropolone 23 or manicol. 24 Of late, oxidopyrylium cycloaddition/ring-opening strategies have emerged that are highly effective for aHTs synthesis 25 and the strategy has been exploited in various medicinal chemistry-based pursuits, including against HSV-1 and -2.…”
Section: Introductionmentioning
confidence: 99%
“…7 During the preparation of this manuscript, a galactose-based method previously used by Sunazuka and Omura to synthesize puberulic acid 8 was further adapted to develop a small library of both 3,7-dHTs and αHTs (Scheme 1B), as well as other related troponoids. 9 Testing of these molecules for their antimalarial activity revealed that a carboxylic acid was key to providing selectivity against Plasmodium falciparum K1 versus MRC-5 cells, and it did so whether on an αHT or a 3,7-dHT, but provided more selectivity with 3,7-dHT. These studies highlight the value in a divergent, unifying strategy in SAR determination of oxygenated troponoids, and their importance in assessing the inhibitory potential of these oxygenated troponoids.…”
Section: Introductionmentioning
confidence: 99%